Evaluation of plasma-activated lactic-gallic acid treated chicken meats on the freshness, volatile changes, and metabolites through multi-analytical techniques - Ismail, Azfar; Lee, Hag Ju; Hong, Suk-Ju; Kim, Ghiseok; Choi, Minwoo; Jo, Cheorun (Elsevier Ltd, 2024)
Various techniques were employed to evaluate freshness, volatile changes, and metabolites in chicken meat treated with plasma-activated lactic-gallic acid. Collectively 96 slices and 216 cubes of chicken breasts and drumsticks were immersed in deionized water (control), a mixture of lactic and gallic acids (0.3 lactic and 0.3 gallic; LGA), plasma-activated deionized water, or PLGA for 10 min. A synergistic effect of plasma was observed with low-concentration LGA in preserving meat quality and color over 8-day aerobic storage (4 °C). On day 8, PLGA-treated breasts and drumsticks exhibited a significant reduction in bacterial spoilage by 0.69 and 0.50 log CFU/g, respectively, compared to control treatment. They also showed the low levels of 2-thiobarbituric acid reactive substances, respectively, as opposed to others. PLGA effectively sanitized and improved meat quality during storage. Multi-analytical techniques revealed strong correlations between anserine and taurine as antioxidants, linking them with freshness and chemical changes in chicken meat. Industrial relevance: Cold atmospheric plasma is FDA-approved for surgical trials, while its potential in the food industry is currently under evaluation and gaining global attention. The combination of plasma and low-concentration lactic-garlic acid (LGA) holds significant promise for expanding markets by preserving color, and fortifying antimicrobial and antioxidant properties of chicken meat. In this study, PLGA treatment enhances chicken meat quality compared to other treatments, reducing microbial growth by up to 17, lowering lipid oxidation by up to 12, and improving volatile changes during storage. Additionally, it establishes a robust foundation for using multi-analytical techniques to correlate chicken meat freshness and chemical changes with direct relevance to the food industry.